p21 differentially regulates DNA replication and DNA-repair-associated processes after UV irradiation - Soria, Ramiro Gaston (2008)
Although p21 upregulation is required to block cell-cycle progression following many types of genotoxic insult, UV irradiation triggers p21 proteolysis. The significance of the increased p21 turnover is unclear and might be associated with DNA repair. While the role of p21 in nucleotide excision repair (NER) remains controversial, recent reports have explored its effect on translesion DNA synthesis (TLS), a process that avoids replication blockage during S phase. Herein, we analyze the effect of p21 on different PCNA-driven processes including DNA replication, NER and TLS. Whereas only the CDK-binding domain of p21 is required for cell-cycle arrest in unstressed cells, neither the CDK-binding nor the PCNA-binding domain of p21 is able to block early and late steps of NER. Intriguingly, through its PCNA-binding domain, p21 inhibits the interaction of the TLS polymerase, pol eta (pol eta), with PCNA and impairs the assembly of pol eta foci after UV. Moreover, this obstruction correlates with accumulation of phosphorylated H2AX and increased apoptosis. By showing that p21 is a negative regulator of PCNA-pol eta interaction, our data unveil a link between efficient TLS and UV-induced degradation of p21.